Penentuan Batasan Penggunaan Informasi Perusahaan yang Digunakan Oleh Mantan Pegawai - Christine S. T. Kansil; Andrea Tamaranova Retaly (Jurnal Hukum Lex Generalis, 2024)
This study examines the determination of limits regarding the use of company information by former employees, and the implementation of the legal protection if such infringement happens based on Law No. 30 of 2000 on Trade Secrets (UURD) and other relevant scholarly studies. The primary focus is to understand the legal boundaries of trade secrets and assess the effectiveness of Non-Disclosure Agreements (NDAs) and Non-Compete Clauses (CNCs). The findings reveal that, although UURD provides a legal framework, its implementation is often unclear, leading to conflicts between protecting trade secrets and the right of former employees to pursue career development. Therefore, a balanced approach is required, emphasizing legal clarity, effective information protection measures, and open communication to safeguard both company interests and individual career rights.